Perlindungan Konsumen Terhadap Jaminan dan Kenyamanan Konsumen Pada Pinjaman Online - Berliana Putri, Debby (Proceedings Series on Social Sciences & Humanities, 2024)
Online loans have become a significant part of today's digital economy, providing quick and easy access to additional funds. However, this growth also  raises concerns about consumer protection regarding collateral and convenience in online loan transactions. This paper explores various aspects of consumer protection  in  the  context  of  online lending,  with  a  focus  on  assurance  and consumer convenience. Through a literature review, it was found that there are significant challenges faced by consumers in understanding and protecting their rights in online loan transactions. Although there are regulations governing this industry, implementation is still uneven and sometimes inadequate. In addition, product complexity and unclear information provided to consumers often create obstacles to achieving adequate protection.